Faktor Yang Memengaruhi Kepatuhan Penderita TB Paru Dalam Mengkonsumsi Obat Di UPT Puskesmas Batang Beruh Kecamatan Sidikalang Kabupaten Dairi - Erida Rohito Lumban Tobing; Nur’aini Nur’aini; Aida Fitria (Journal of Educational Innovation and Public Health, 2024)
Indonesia's Health Profile in 2022, there were 845,000 cases of pulmonary TB and in 2021 there were 420,994 cases. There were 563,879 new confirmed cases of pulmonary TB and relapses. If this is not adhered to, it will cause drug resistance. The aim of the research was to determine the factors that influence the compliance of pulmonary TB sufferers in taking medication at the Batang Beruh Health Center UPT, Sidikalang District, Dairi Regency. The research design uses an analytical survey research method with a cross sectional research design. The population in this study was all 126 pulmonary TB patients. The sample was 56 people with a purposive sampling method. Data analysis uses univariate, bivariate and multivariate analysis. The results of the study showed that there was an influence of knowledge p = 0.010, attitude p = 0.006, family support p = 0.000 and drug side effects p = 0.000, while the variable that had no influence was gender, p = 0.057, on the compliance of pulmonary TB sufferers in taking medication. at UPT Batang Beruh Community Health Center, Sidikalang District, Dairi Regency, while the dominant factor was family support, p = 0.006 < 0.025, 95% CI = 2.715-519.110 and OR = 37.543. The conclusion is that there is an influence of knowledge, attitude, family support and side effects of drugs, while the variable that has no influence is gender on the compliance of pulmonary TB sufferers in taking drugs at UPT Puskesmas Batang Beruh, Sidikalang District, Dairi Regency. Recommended to UPT. Batang Beruh Community Health Center, Sidikalang District, increases public knowledge about pulmonary TB among sufferers and visiting residents by providing outreach and providing information on the SITB application. Targets at risk of contracting pulmonary TB are the sufferer's family and health workers. And as a Medicine Taking Supervisor are the families of pulmonary TB sufferers.